Structures of two lyssavirus glycoproteins trapped in pre- and post-fusion states and the implications on the spatial-temporal conformational transition along with pH-decrease. - Fanli Yang; Sheng Lin; Xin Yuan; Siqi Shu; Yueru Yu; Jing Yang; Fei Ye; Zimin Chen; Bin He; Jian Li; Qi Zhao; Haoyu Ye; et al. (PLoS Pathogens)
Lyssavirus glycoprotein plays a crucial role in mediating virus entry and serves as the major target for neutralizing antibodies. During membrane fusion, the lyssavirus glycoprotein undergoes a series of low-pH-induced conformational transitions. Here, we report the structures of Ikoma lyssavirus and Mokola lyssavirus glycoproteins, with which we believe that we have trapped the proteins in pre-fusion and post-fusion states respectively. By analyzing the available lyssaviral glycoprotein structures, we present a sequential conformation-transition model, in which two structural elements in the glycoprotein undergo fine-modulated secondary structural transitions, changing the glycoprotein from a bended hairpin conformation to an extended linear conformation. In addition, such conformational change is further facilitated, as observed in our surface plasmon resonance assay, by the pH-regulated interactions between the membrane-proximal region and the pleckstrin homology and the fusion domains. The structural features elucidated in this study will facilitate the design of vaccines and anti-viral drugs against lyssaviruses.